2021
DOI: 10.1021/acs.jafc.0c07839
|View full text |Cite
|
Sign up to set email alerts
|

Konjac Oligosaccharides Modulate the Gut Environment and Promote Bone Health in Calcium-Deficient Mice

Abstract: This study aimed to investigate the beneficial effect of konjac oligosaccharides (KOS) on bone health in calcium-deficient mice. During the experimental period, low-calcium diet-fed mice were administered with calcium chloride to simulate daily calcium supplementation. Meanwhile, different levels of KOS intervened by adding them into the diet. After 8 weeks, the calcium balance status, bone mass parameters, and gut environment modulation were evaluated. The results showed that dietary KOS intervention alleviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…Untargeted metabolomics based on HPLC–MS/MS is an efficient tool for probing hundreds of metabolites even in low quantities and has been applied to detect metabolites in fecal samples . By analyzing the HPLC–MS/MS data, we removed the values of the medium components and screened the significant metabolites in each medium (Tables S2–S6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Untargeted metabolomics based on HPLC–MS/MS is an efficient tool for probing hundreds of metabolites even in low quantities and has been applied to detect metabolites in fecal samples . By analyzing the HPLC–MS/MS data, we removed the values of the medium components and screened the significant metabolites in each medium (Tables S2–S6).…”
Section: Resultsmentioning
confidence: 99%
“…Untargeted metabolomics based on HPLC−MS/MS is an efficient tool for probing hundreds of metabolites even in low quantities and has been applied to detect metabolites in fecal samples. 39 By analyzing the HPLC− MS/MS data, we removed the values of the medium components and screened the significant metabolites in each medium (Tables S2−S6). HPLC−MS/MS-based metabolomics analysis revealed that the metabolites screened from different media were significantly different, which suggested that various microbial-fermented media greatly affect the metabolic profile of gut microbiota.…”
Section: ■ Introductionmentioning
confidence: 99%
“…94 Konjac oligosaccharide displayed the beneficial effect of prebiotics on bone health: dietary konjac oligosaccharide intervention in low-calciumdiet-fed mice alleviated the negative calcium balance, significantly promoted the cortical thickness and trabecular number, and remarkably enhanced the mechanical strength of the skeleton. 95 On the basis of published data, it can be concluded that KGM, Da-KGM, and degraded KGM derivatives at an appropriate dosage potentially improved health as a result of their colloidal nutritional effect (Figures 3 and 4). However, overconsumption of KGM and degraded KGM derivatives might cause flatulence and even lead to an imbalance of nutrients.…”
Section: Colloidal Nutritionmentioning
confidence: 97%
“…In addition, konjac oligosaccharide attenuated severity of 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced colitis in rats as a result of its anti-inflammatory and prebiotic effects . Konjac oligosaccharide displayed the beneficial effect of prebiotics on bone health: dietary konjac oligosaccharide intervention in low-calcium-diet-fed mice alleviated the negative calcium balance, significantly promoted the cortical thickness and trabecular number, and remarkably enhanced the mechanical strength of the skeleton …”
Section: Colloidal Nutritionmentioning
confidence: 99%
“…Prebiotics can selectively influence and modify GM composition by promoting the growth of certain microorganisms. Several recent studies have shown that prebiotics such as Konjoc oligosaccharides, GOS, FOS can significantly enhance bone mass by reversing dysbiosis ( Ai et al, 2021 ; Zhang et al, 2021 ). Prebiotics also enhance bone mass by decreasing intestinal permeability and thus preventing systemic inflammation ( Zhang et al, 2021 ).…”
Section: Dietary Interventions and Modulation Of Gut Microbiotamentioning
confidence: 99%